2022
DOI: 10.1111/ijfs.15553
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity assessment of Yingjisha sweet almond oil

Abstract: Sweet almond is one of the main cash crops in Yingjisha, Xinjiang Autonomous Region, China. The composition of sweet almond oil (SAO) was analysed by gas chromatography-mass spectrometry (GC-MS). SAO's antioxidant activities were investigated by measuring its scavenging ability with 1,1-diphenyl-2picrylhydrazyl (DPPH), 2,2 0 -Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), hydroxyl radical scavenging assay and 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox) equivalent antioxidant cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The antioxidant nature of AO effects may result from its unique composition in antioxidants and unsaturated fatty acids, which contribute to cell membranes stabilization and repair of brain and liver tissue damage caused by LPS [40]. As reported for several edible oils, the unsaturated fatty acids display also antioxidant properties [41]. Earlier work of Khalouki et al [12] reported the antioxidant profile of argan oil, showing that AO phenolic compounds exhibit an antioxidant capacity superior to the soluble form of vitamin E, Trolox [12].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The antioxidant nature of AO effects may result from its unique composition in antioxidants and unsaturated fatty acids, which contribute to cell membranes stabilization and repair of brain and liver tissue damage caused by LPS [40]. As reported for several edible oils, the unsaturated fatty acids display also antioxidant properties [41]. Earlier work of Khalouki et al [12] reported the antioxidant profile of argan oil, showing that AO phenolic compounds exhibit an antioxidant capacity superior to the soluble form of vitamin E, Trolox [12].…”
Section: Discussionmentioning
confidence: 93%
“…However, AO showed a more pronounced decrease in MDA production in both brain and liver tissues. As mentioned above, it is noteworthy that AO harbors one of the highest antioxidant capacities among edible oils, including melatonin, coenzyme Q 10 , tocopherols, and ferulic acid [11,[37][38][39][40][41][42][43][44]. The antioxidant nature of AO effects may result from its unique composition in antioxidants and unsaturated fatty acids, which contribute to cell membranes stabilization and repair of brain and liver tissue damage caused by LPS [40].…”
Section: Discussionmentioning
confidence: 98%